Aksiologi Pendidikan Islam Perspektif Al Ghozali Intisari Yang Terpinggirkan Dalam Potret Pendidikan Islam Indonesia Modern - Arif Wibowo (AL-MUTSLA, 2026)
There are many types of education in modern times. There is international standard education, bilingual education, ‘graduate ready to work’ education and so on. This is all because it starts with the assumption of a person’s ‘success’ or what a person is considered successful. Starting from the word ‘success’, this eventually gives birth to the goals that will be achieved. For those who assume success as well as the same as those abroad, for example, then the same curriculum is made as abroad. So that when the ability is the same as those abroad, it can be considered successful or great. Likewise, the language that can be mastered or success is considered when working, so the curriculum or vision and mission of an education is determined. This research method is a type of qualitative research directed at the exploration of library research. Which includes systematic identification, analysis of documents that contain information related to the problem of study, namely the axiology of Islamic education in the perspective of al Ghozali to address the reality of education in Indonesia today. Actually, 1,445 years ago, rosulullah has conveyed the main purpose of being sent to mankind, which is to perfect good morals. Good character here is a supreme awareness, positioning oneself as a servant to carry out orders and stay away from His prohibitions and as a creature can socialise with fellow creations of Allah as well as possible. So the success that Allah expects through the treatise to the rosulullah is a person who increasingly knows Allah, His commands and prohibitions, as whatever our role in this world.